Be careful with ecological associations. Issue 6 (17th February 2021) - Roumeliotis, Stefanos; Abd ElHafeez, Samar; Jager, Kitty J.; Dekker, Friedo W.; Stel, Vianda S.; Pitino, Annalisa; Zoccali, Carmine; Tripepi, Giovanni
Abstract: Ecological studies are observational studies commonly used in public health research. The main characteristic of this study design is that the statistical analysis is based on pooled (i.e., aggregated) rather than on individual data. Thus, patient‐level information such as age, gender, income and disease condition are not considered as individual characteristics but as mean values or frequencies, calculated at country or community level. Ecological studies can be used to compare the aggregated prevalence and incidence data of a given condition across different geographical areas, to assess time‐related trends of the frequency of a pre‐defined disease/condition, to identify factors explaining changes in health indicators over time in specific populations, to discriminate genetic from environmental causes of geographical variation in disease, or to investigate the relationship between a population‐level exposure and a specific disease or condition. The major pitfall in ecological studies is the ecological fallacy, a bias which occurs when conclusions about individuals are erroneously deduced from results about the group to which those individuals belong. In this paper, by using a series of examples, we provide a general explanation of the ecological studies and provide some useful elements to recognize or suspect ecological fallacy in this type of studies. SUMMARY AT A GLANCE: This article describes the application of ecological studies to provide an answer to specific epidemiological questions. This paper focuses on the problem of ecological fallacy, a bias which occurs when conclusions about a given relationship in individuals are deduced from inferences about the group to which those individuals belong.